Dopamine regulation of contextual fear and associated neural circuit function. (20th May 2020) - Stubbendorff, Christine; Stevenson, Carl W.
Abstract: Learning to associate certain contexts with threat and adapting to changing environmental contingencies by learning that such contexts are no longer associated with threat are both crucial for survival. Research over the last few decades has made considerable progress in determining the brain areas involved in the encoding, retrieval and extinction of contextual fear. These studies have identified the hippocampus and amygdala, along with the prefrontal cortex and other inter‐connected brain areas, as key players in contextual fear processing. In contrast to the neural circuit basis of contextual fear, the neurochemical mechanisms involved in its regulation remain poorly understood. Dopamine is well known for its role in appetitive learning but this neurotransmitter is also important for other types of learning, including spatial and aversive memory processing. Dopamine is ideally positioned to regulate contextual fear given that the areas involved receive dopamine input and express dopamine receptors. Moreover, neuronal activity, functional connectivity and synaptic plasticity in this neural circuitry are modulated by dopamine receptor signalling. Here, we review the evidence indicating that dopamine regulates various contextual fear processes, along with the more recent studies that have begun to elucidate the brain areas and neurophysiological mechanisms involved. From a fundamental research perspective, understanding how dopamine regulates contextual fear will lead to novel insights on the neurochemical modulation of neural circuit function underlying memory processing. This research may also have translational relevance given that contextual fear conditioning and extinction also provide useful preclinical models of certain aspects of anxiety‐related disorders and their treatment. Abstract : Dopamine is important for regulating contextual fear processing. D1‐like receptors throughout the contextual fear circuit are involved in contextual fear conditioning, extinction and later fear relapse. D2‐like receptors are involved in contextual fear retrieval but their role in other contextual fear processes is unclear. Determining how dopamine regulates contextual fear will lead to a better understanding of neuromodulation of neural circuit function underlying memory processing.